Analisis Motivated Strategies for Learning Questionnaire pada Mahasiswa Program Kartu Indonesia Pintar-Kuliah - Farida Aini; Rizky Qastrunada Fatria (Jurnal Ilmiah Psikologi MIND SET, 2023)
Self-regulation in learning is one of the supporting factors for every student to achieve optimal learning outcomes, involved for the college students who receive the Kartu Indonesia Pintar (KIP-Smart Indonesian Cardi)-Kuliah (College) Program. The Motivated Strategies for Learning Questionnaire (MSLQ) questionnaire is one of the questionnaires to measure self-regulation in learning which was developed by Pintrich and De Groot (1990). The questionnaire consists of 81 items. Researchers have adapted it. This research aims to determine the validity and reliability of the questionnaire, besides that, the research aims to analyze the MSLQ as one-dimensional or multidimensional. The analyzed MSLQ instrument used the Rasch Model. Respondents for this research are 1258 students who came from 14 universities spread across 4 cities/districts. The validity test showed that 68 items were valid and 13 items were invalid with a reliability value of 0.95. The results of the one-dimensional test found that the raw variance explained by measure value was 36.7%, close to the expected value of 35.8%, this value is the sufficient category to be said to have one-dimensional. This research concludes that the MSLQ questionnaire is suitable for measuring self-regulation in learning for college students.